2014
DOI: 10.1167/iovs.14-14937
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Longitudinal Study of Retinal Structure and Function in Achromatopsia

Abstract: Previously published cross-sectional studies have described conflicting findings with respect to the age-dependency of progression. This study, which constitutes the largest and longest prospective longitudinal study of ACHM to date, suggests that although ACHM may be progressive, any such progression is slow and subtle in most patients, and does not correlate with age or genotype. We also describe the first serial assessment of FAF, which is highly variable between individuals, even of similar age and genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
4
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(134 citation statements)
references
References 41 publications
10
117
4
3
Order By: Relevance
“…Our identification of distinct pathomechanisms of ATF6 disease mutations enables prospective longitudinal study of retinal structure and phenotype to identify possible differences in achromatopsia disease phenotype and severity between carriers with different classes of ATF6 mutations. Evaluation with adaptive optics and other retinal imaging modalities may reveal cone phenotype differences corresponding to different classes of ATF6 mutations (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Our identification of distinct pathomechanisms of ATF6 disease mutations enables prospective longitudinal study of retinal structure and phenotype to identify possible differences in achromatopsia disease phenotype and severity between carriers with different classes of ATF6 mutations. Evaluation with adaptive optics and other retinal imaging modalities may reveal cone phenotype differences corresponding to different classes of ATF6 mutations (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies in recent years have investigated outer retinal architecture and foveal morphology in detail using high-resolution optical coherence tomography (OCT) and adaptive optics [12,13,14,27,29,30,31,32,33,34]. The macular appearance in OCT can show either normal lamination or variable degrees of disruption of the photoreceptor layers and loss of retinal pigment epithelium.…”
Section: Clinical Manifestation and Diagnosticsmentioning
confidence: 99%
“…In recent years, several studies have investigated photoreceptor morphology in ACHM [29,30,31,32,33,34]. Carroll et al [32] observed a severely disrupted cone mosaic in the fovea and parafoveal area of a single patient with mutations in CNGB3.…”
Section: Some Inconsistencies Regarding the Progressive Nature Of Mormentioning
confidence: 99%
See 2 more Smart Citations